IMPLEMENTASI PROFIL PELAJAR PANCASILA DI KELAS IV SD NEGERI SUKOMANGLI 01 - Bambang arifianto; Arri Handayani; Dini Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to analyze the implementation of the Pancasila student profile in grade 4 of SD Negeri Sukomangli 01. This study applies a qualitative approach with a naturalistic type of inquiry method. The subjects in this research were the school principal, class 4 teachers, and class 4 students at SD Negeri Sukomangli 01. The method of data collection was carried out by non-test through questionnaires. The instrument used is a questionnaire sheet. Data analysis methods include information gathering, subtraction, presentation, and drawing conclusions. The implication of this research is that the application of the Pancasila profile among elementary school students can improve their character. The results of the analysis of this research data show that the percentage scores for the implementation of the Pancasila student profile in six different aspects. Each aspect is described as believing, fearing God Almighty has a score percentage of 85%. The second aspect of global diversity has a percentage of 70%. The third aspect of mutual assistance has a percentage of 82%. The fourth aspect is independent and has a percentage of 76%. The fifth aspect of critical thinking has a percentage of 68%. The creative sixth aspect has a percentage of 79%. The implementation of the Pancasila student profile is carried out through habits which are divided into routine habits and spontaneous habits. The implication of this research is that applying the Pancasila profile to elementary school students can strengthen the character of students.